Functional Analysis of Glycosyltransferase Genes from Lactococcus lactis and Other Gram-Positive Cocci: Complementation, Expression, and Diversity - van Kranenburg, Richard (American Society for Microbiology, 1999)
Sixteen exopolysaccharide (EPS)-producing Lactococcus lactis strains were analyzed for the chemical compositions of their EPSs and the locations, sequences, and organization of the eps genes involved in EPS biosynthesis. This allowed the grouping of these strains into three major groups, representatives of which were studied in detail. Previously, we have characterized the eps gene cluster of strain NIZO B40 (group I) and determined the function of three of its glycosyltransferase (GTF) genes. Fragments of the eps gene clusters of strains NIZO B35 (group II) and NIZO B891 (group III) were cloned, and these encoded the NIZO B35 priming galactosyltransferase, the NIZO B891 priming glucosyltransferase, and the NIZO B891 galactosyltransferase involved in the second step of repeating-unit synthesis. The NIZO B40 priming glucosyltransferase gene epsD was replaced with an erythromycin resistance gene, and this resulted in loss of EPS production. This epsD deletion was complemented with priming GTF genes from gram-positive organisms with known function and substrate specificity. Although no EPS production was found with priming galactosyltransferase genes from L. lactis or Streptococcus thermophilus, complementation with priming glucosyltransferase genes involved in L. lactis EPS and Streptococcus pneumoniae capsule biosynthesis could completely restore or even increase EPS production in L. lactis.